EFEKTIVITAS BADAN KEPEGAWAIAN DAERAH SIMEULUE DALAM PELAKSANAAN TINDAKAN ADMINISTRATIF DAN HUKUMAN DISIPLIN TERHADAP PEGAWAI NEGERI SIPIL YANG MENGGUNAKAN IJAZAH PALSU - Cut Sara (Prodi Ilmu Hukum, Universitas Teuku Umar, 2025)
The use of fake diplomas has become a problem that has attracted the attention of the public, where there are 112 civil servants who use fake diplomas in several Simeulue Regency regional government agencies when registering as CPNS or applying for positions. This research aims to look at the effectiveness of implementing administrative actions and disciplinary penalties against civil servants who use fake diplomas, as well as looking at the factors that influence the implementation of disciplinary penalties against civil servants who use fake diplomas in Simeulue Regency. This research uses empirical juridical methods with a statutory regulation approach and a case approach. The results of the research show that in Government Regulation Number 94 of 2021 concerning Civil Servant Discipline, Article 8 paragraph (1) states the levels and types of disciplinary punishment, namely: light, medium and heavy disciplinary punishment. The implementation of administrative actions and disciplinary penalties against civil servants who use fake diplomas in Simeulue Regency has not been effective, because it is influenced by several factors, namely humanitarian considerations and avoiding social impacts. With these considerations, disciplinary punishment is ineffective because it does not have a deterrent effect on the 112 civil servants and does not rule out the possibility of diploma falsification in the future. It is recommended that the Regional Government be morefirm in providing disciplinary punishments to employees who are proven to have used fake diplomas, so that the law can run effectively and be able to prevent acts of diploma forgery.